Increasing Export Diversification in Commodity-Exporting Countries : A Theoretical Analysis - DeRosa, Dean (IMF Working Papers; Working Paper ;, 1991)
This paper draws on the neoclassical theory of international trade to examine the limits of efficient export diversification in low-income, commodity-exporting countries. It demonstrates the fundamental importance of relative factor endowments among countries for determining the commodity composition of international trade flows under both certain and uncertain economic conditions. In recognition of the importance of international financial markets for risk-spreading and allocating resources efficiently under uncertainty, the paper emphasizes the importance of 'open' economic policies towards international trade in financial assets as well as goods.